Cyclodextrins in Parkinson's Disease - Barros, Marisa C. F. (2018)
Parkinson's disease is a movement disorder characterized by a progressive degeneration of dopaminergic neurons that has been object of study by the scientific community through the last decades. However, nowadays there is still no treatment to cure it, although there are drugs available, with limited efficacy, to relieve the symptoms or replenish the cells with dopamine to supply the lack of dopaminergic neurons. This work was structured in two parts. In the first one, binary aqueous solutions of L-dopa and cyclodextrins were studied. In the second part, ternary aqueous solutions of L-dopa were studied with each of the selected cyclodextrins. In all cases, thermodynamic properties (density, partial molar volume and thermodynamic transfer functions for temperatures between 294.15 ± 0.01 K and 312.15 ± 0.01 K) and transport properties (mutual diffusion coefficients, viscosity, transfer viscosity at 298.15 ± 0.01 K and 310.15 ± 0.01 K) were studied. Using theoretical models to adjust the experimental data obtained for the diffusion coefficients and for the apparent molar volumes, in the ternary aqueous solutions, it was possible to estimate the values to the L-dopa-cyclodextrin association constant. For the aqueous ternary solutes, the partial molar volume of transfer of levodopa in the presence of the cyclodextrins, the partial molar expansibility at infinite dilution and from this, the Hepler constant, were determined. Also, the values of Gibbs free energy (ΔG⁰), enthalpy (ΔH⁰) and entropy (ΔS⁰) were determined. From the obtained information, it was possible to characterize the molecular interactions, as well as to identify some structural characteristics of the controlled drug delivery systems under study and to estimate the influence of the cyclodextrin substituent groups, and, also, the temperature effect in the interaction levodopa-cyclodextrin. It is our intent to attain information about the mechanism of possible new systems for controlled drug delivery systems, throughout an alternative perspective, which could allow to increase its effectiveness in the Parkinson's treatment.